Moving businesses online and embracing e-commerce impact and opportunities caused by COVID-19 - Semerádová, Tereza, 1989-; Weinlich, Petr, 1976- (Advances in electronic commerce series., 2022)
"This publication analyzes the impacts of COVID-19 related restrictions on the business models of enterprises affected by these restrictions, putting an emphasis on the transformational changes induced by the accelerated adoption of Internet technologies and transition to e-commerce based business models"--